Corporate greenwashing : are environmental claims just empty promises? - Isaacs, Andrew M.; Coromina, Natàlia Costa I. (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2022)
Greenwashing is a term used to describe situations where a company's environmental claims go beyond what the company has achieved through its environmental commitments. Greenwashing has been found to have reached 'fashionable' proportions. As a result, consumers, investors, employees, and other stakeholders cannot be sure which environmental claims impact the fight against climate change and which are irrelevant, leading to lack of trust. This case study includes examples of corporate environmental efforts. These examples and associated case study questions are designed to support students in assessing whether Greenwashing is being committed by a corporation, and the form in which it may be occurring.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business enterprises -- Environmental aspects -- Case studies; Greenwashing -- Case studies; Business ethics -- Case studies